Pengaruh Ukuran Perusahaan dan Good Corporate Governance Terhadap Underpricing Saham Pada Saat Initial Public Offering Pada Perusahaan Non-Keuangan yang Terdaftar di BEI Periode 2009-2012 - Mira Agulina; Haryetti '; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Underpricingis a phenomenon that of tenoccurs incompanies doing IPOsin the stock market and has been demonstrated by several previous researchers. This study aimsto examine the effect of firm size and good corporate governance inproxied is Audit Committee, Managerial Ownership and Institutional Ownership on the stockat the time of IPO Underpricing. This research conducted in companies doing IPO at Indonesia Stock Exchange in the non-financial companies in period of 2009–2012. Underpricing in this research is the dependent variable, while the independent variable in this research is the firm size and good corporate governance isproxied Audit Committee, Managerial ownership and Institutional Ownership. Sample is collected by using purposive random sampling, resulting in 54 companies assample. Multiple regression analysis model used to test relation between independent variables and dependent variable. Regression analysis shows that the variables of firm size and managerial ownership of IPO fund have negative and significant influence on the level of underpricing. While institusioal ownership and audit committee do not have significant influence to underpricing. This result had implication that: 1) companies doing IPO should consider the rirm size and managerial ownership of using IPO fund to attract investors and minimize the level of underpricing, 2) investors should consider both variables in their IPO investment decision in order to get higher returnKeywords: Underpricing, Initial Public Offering, Firm Size, Good Corporate Governance, Audit Committee, Managerial Ownership, Institutional Ownership